Effect of Publicly Reported Aortic Valve Surgery Outcomes on Valve Surgery in Injection Drug– and Non–Injection Drug–Associated Endocarditis. (10th October 2019) - Kimmel, Simeon D; Walley, Alexander Y; Linas, Benjamin P; Kalesan, Bindu; Awtry, Eric; Dobrilovic, Nikola; White, Laura; LaRochelle, Marc
Abstract: Background: Injection drug use–associated infective endocarditis (IDU-IE) is rising and valve surgery is frequently indicated. The effect of initiating public outcomes reporting for aortic valve surgery on rates of valve surgery and in-hospital mortality for endocarditis is not known. Methods: For an interrupted time series analysis, we used data from the National Inpatient Sample, a representative sample of United States inpatient hospitalizations, from January 2010 to September 2015. We included individuals aged 18–65 with an International Classification of Diseases, Ninth Revision (ICD-9) diagnosis of endocarditis. We defined IDU-IE using a validated combination of ICD-9 codes. We used segmented logistic regression to assess for changes in valve replacement and in-hospital mortality rates after the public reporting initiation in January 2013. Results: We identified 7322 hospitalizations for IDU-IE and 23 997 for non–IDU-IE in the sample, representing 36 452 national IDU-IE admissions and 119 316 non-IDU admissions, respectively. Following the implementation of public reporting in 2013, relative to baseline trends, the odds of valve replacement decreased by 4.0% per quarter (odds ratio [OR] 0.96, 95% confidence interval [CI] 0.93–0.99), with no difference by IDU status. The odds of an in-patient death decreased by 2.0% per quarter for both IDU-IE and non–IDU-IE cases following reporting (OR 0.98, 95% CI 0.97–0.99). Conclusions: Initiating public reporting was associated with a significant decrease in valve surgery for all IE cases, regardless of IDU status, and a reduction in-hospital mortality for patients with IE. Patients with IE may have less access to surgery as a consequence of public reporting. To understand how reduced valve surgery impacts overall mortality, future studies should examine the postdischarge mortality rate. Abstract : In this interrupted time-series analysis of United States hospitalizations, the initiation of public reporting of aortic valve surgery outcomes in 2013 was associated with a 4.0% decrease in odds of surgery per quarter, with no differences by injection drug status.